2014
DOI: 10.3390/s141017915
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Healthcare for Automatic Driving Sleep-Onset Detection Using Wavelet-Based EEG and Respiration Signals

Abstract: Driving drowsiness is a major cause of traffic accidents worldwide and has drawn the attention of researchers in recent decades. This paper presents an application for in-vehicle non-intrusive mobile-device-based automatic detection of driver sleep-onset in real time. The proposed application classifies the driving mental fatigue condition by analyzing the electroencephalogram (EEG) and respiration signals of a driver in the time and frequency domains. Our concept is heavily reliant on mobile technology, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 23 publications
7
86
0
3
Order By: Relevance
“…In this context, the present study examined the effect of inhalation of geosmin and 2-methylisoborneol on the human EEG activity in relation to brain functions. In the EEG study, delta (0-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma are the most important brain waves used to understand the role of odors in the psychological and physiological conditions of humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the present study examined the effect of inhalation of geosmin and 2-methylisoborneol on the human EEG activity in relation to brain functions. In the EEG study, delta (0-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma are the most important brain waves used to understand the role of odors in the psychological and physiological conditions of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Beta waves play a major role in the enhancement of cognitive performances in humans. An increase in beta activity is associated with alertness and concentration states of brain [21]. In the posterior regions, increase in beta wave activity is highly related to the enhancement of reading speed, reorganization of language, and rhythm-learning task [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the optimization problem is relatively straightforward [18]. Several recent studies have demonstrated the usefulness of SVMs in the framework of SAHS management [102][103][104][105]. Moreover, in the present research, some studies were reviewed reporting that SVM-based classifiers reached higher accuracy than ANNs [23,45,52].…”
Section: Resultsmentioning
confidence: 99%
“…The current trend is to include various smart devices, such as smartphones and tablets in the configuration of hospital systems [13][14][15]. A majority of studies facilitates real-time information sharing among smart devices through a medical information-sharing framework based on hybrid applications (apps) [16][17][18].…”
Section: Hospital Information System Based On Smart Devicesmentioning
confidence: 99%